Primary resistance to integrase strand transfer inhibitors in patients infected with diverse HIV-1 subtypes in sub-Saharan Africa. (14th February 2018) - Inzaule, Seth C; Hamers, Raph L; Noguera-Julian, Marc; Casadellà, Maria; Parera, Mariona; Rinke de Wit, Tobias F; Paredes, Roger
Abstract: Objectives: To investigate the prevalence and patterns of major and accessory resistance mutations associated with integrase strand transfer inhibitors (INSTIs), across diverse HIV-1 subtypes in sub-Saharan Africa. Methods: pol gene sequences were obtained using Illumina next-generation sequencing from 425 INSTI-naive HIV-infected adults from Kenya (21.2%), Nigeria (7.3%), South Africa (22.8%), Uganda (25.2%) and Zambia (23.5%). Drug resistance interpretation was based on the IAS 2017 mutation list and accessory mutations from Stanford HIVdb with resistance penalty scores of ≥10 to at least 1 INSTI. Resistance was further classified based on sensitivity thresholds of ≥20% (Sanger sequencing) and 1%–20% for low-frequency variants (next-generation sequencing). Results: Of 425 genotypes, 48.7% were subtype C, 28.5% A, 10.1% D, 2.8% G and 9.9% were recombinants. Major INSTI resistance mutations were detected only at <20% threshold, at a prevalence of 2.4% (2.5% in subtype A, 2.4% C, 0% D, 8.3% G and 2.4% in recombinants) and included T66A/I (0.7%), E92G (0.5%), Y143C/S (0.7%), S147G (0.2%) and Q148R (0.5%). Accessory mutations occurred at a prevalence of 15.1% at the ≥20% threshold (23.1% in subtype A, 8.7% C, 11.6% D, 25% G and 23.8% in recombinants), and included L74I/M (10.4%), Q95K (0.5%), T97A (4%), E157Q (0.7%) and G163R/K (0.7%). Conclusions: Major INSTI resistance mutations were rare and only occurred at low-level resistance detection thresholds. INSTI-based regimens are expected to be effective across the different major HIV-1 subtypes in the region.